A simplified model for linear correlation between annual yield and DNI for parabolic trough collectors. (15th October 2018) - Ahlgren, Benjamin; Tian, Zhiyong; Perers, Bengt; Dragsted, Janne; Johansson, Emma; Lundberg, Kajsa; Mossegård, Jonatan; Byström, Joakim; Olsson, Olle
Highlights: Case study for 316 climate station conditions was carried out. Strong linear dependence on total yearly DNI was found. Simplified model shows accurate results in 12 latitudes worldwide. Abstract: This paper proposes a simple method for estimating annual thermal performance of parabolic trough collectors (PTCs) based on a linear relation with annual DNI for a certain latitude. A case study with simulations for a novel concentrating solar collector in 316 locations for three operating temperature scenarios worldwide was carried out and showed promising results for the latitudes and continents investigated. For a certain latitude and mean operating temperature, the annual yield of a PTC was found to be linearly proportional to yearly DNI. The proposed method will serve as a simplified alternative to the steady-state and quasi-dynamic methods already used. Estimating performance based on yearly DNI can be used by design engineers to do quick preliminary planning of solar plants. Customers can also use this method to evaluate existing solar collector installations. A TRNSYS/TRNSED tool that uses a steady-state model has been developed to carry out the simulations and it has been validated against a PTC array at Technical University of Denmark (DTU). The results show that the simplified method can give reliable estimates of long-term performance of parabolic trough collectors.